The Effects of Hydroalcoholic Extract of Pinus eldarica on Hippocampal Tissue Oxidative Damage in Pentylenetetrazole-Induced Seizures in Rat - Bargi, Rahimeh; Asgharzadehyazdi, Fereshteh; Beheshti, Farimah; Mousavi, S. M.; Langehbiz, Shabnam Vafadar; Rakhshandeh, Hassan; Sadeghnia, Hamid Reza; Hosseini, Mahmoud (Current Nutrition & Food Science, 2017)
Background: Brain tissues oxidative damage has been proposed to occur as a result of epileptic seizures. With respect to the antioxidant effects of Pinus eldarica (P. eldarica), the impacts of a hydroalcoholic extract of the plant on the brain tissues oxidative damage taking after seizures induced by Pentylenetetrazole (PTZ) was investigated in rats. Methods: The rats were divided into 6 groups and treated: (1) Control(saline); (2) PTZ (100 mg/kg, i.p.), [3-6] four doses including 20, 50, 200 and 500 mg/kg of P. eldarica extract (Ext 20, Ext 50, Ext 200, Ext 500) 30 min before PTZ injection. Latencies to the first Minimal Clonic (MCS) and Generalized Tonic-Clonic (GTCS) seizures were recorded. The hippocampal tissues were then collected for biochemical measurements. Results: The extract non-significantly postponed both the MCS and GTCS onsets. PTZ- induced seizure increased Malondialdehyde (MDA) (P<0.001) concentration while, diminished thiol contents (P<0.01) of hippocampal tissues. Pretreatment with 200 mg of the extract diminished MDA level in the hippocampal tissues compared to the PTZ group (P<0.001). Both 50 and 200 mg/kg of the extract improved thiol concentration in the hippocampal tissues (p<0.01). Conclusion: The present study demonstrated that the extract of P. eldarica possess protective effects against hippocampal tissues oxidative damage in PTZ- induced seizure model.
Keywords: pentylenetetrazole